Effect of anlotinib combined with ticeorgio for recurrent nasopharyngeal carcinoma: a case report - Mao, Jiwei; Ye, Wanli; Wu, Dongping; Liu, Jianjiang; Li, Ting; Ma, Weili; Zhou, Yang (Frontiers in Pharmacology, 2023)
For patients with locally unresectable recurrent nasopharyngeal carcinoma who relapsed after 2 years of radiotherapy, re-radiotherapy is also the preferred treatment. However, for patients relapsed within 2 years, the use of re-radiotherapy would be greatly limited by its adverse effects. Consequently, finding a new strategy to prolong the time of re-radiotherapy for locally recurrent nasopharyngeal carcinoma is very necessary to reduce the related side effects and improve the curative effect. Anlotinib is an orally available small molecule multi-target tyrosine kinase inhibitor that primarily inhibits VEGFR2/3, FGFR1–4, PDGFR α/β, c-Kit, and Ret. However, whether recurrent nasopharyngeal carcinoma patients can be treated with anlotinib combined with ticeorgio (also called S-1) remains unknown. Herein, we report a nasopharyngeal carcinoma patient with local recurrence after radical radiotherapy who benefited from combination treatment of anlotinib with ticeorgio.